INTEGRASI NILAI ISLAM DALAM PEMBELAJARAN IPA (Perspektif Pendidikan Islam) - Novianti Muspiroh (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This paper aims to examine the possibility of spiritual values that is integrated with subject-matter of general subjects, especially science (IPA). The method of analysis in this paper adopts the basic principles of values education in Islam is monotheism, science and morals, which is based on the integration of knowledge between public science with the science of religion (non-dichotomous). Integration of Islamic values in the science learning manifest in the pattern of the overall science learning (integral-holistic) appreciates the existence of a general science or science as the study of Islamic religious knowledge as well as responding to the needs of society and the family. In regard to the implementation of learning the values of unity, stimulating science search continuously and pay attention to aspects of students' moral and noble character.